Perkawinan Poligami dan Dasar Hukumnya dalam Alquran dan Hadist - Parlagutan Hasibuan; Kasman Sofyan; Ahmad Fauzi (Suria Academic Press, 2026)
The issue of polygamy in Islamic law often stems from a partial interpretation of the Qur’anic and Hadith texts that neglects the socio-historical context of revelation and the complexity of their universal moral messages. This tendency has led to a polarized discourse between absolute justification and radical rejection. Departing from this problem, the present study aims to analyze the legal foundations of polygamy in a comprehensive and contextual manner in order to produce a holistic understanding and to propose an evaluative framework oriented toward the principle of justice. This study employs a library research approach analyzed through Fazlur Rahman’s contextual hermeneutical framework, involving a three-stage analysis: historical-critical examination, extraction of moral principles, and contextual application to key Qur’anic verses and relevant authentic Hadiths. The findings indicate that the legal basis of polygamy in the Qur’an and the Sunnah is ultra-restrictive, functioning as a conditional solution burdened by the requirement of holistic justice that is nearly impossible to fulfill perfectly. Consequently, its normative spirit aligns more closely with monogamy. The novelty of this research lies in its integrative synthesis that connects the internal dialectics of the texts, the evolution of juridical interpretations across Islamic legal schools, and contemporary principles of public welfare (maslahah) within a coherent analytical framework, offering a constructive middle path that remains grounded in textual authority while being responsive to modern ethical values.